The role of talk shows in influencing the public’s priorities regarding political mobilization in Iraq - Fakher, Alia Adel; Al-Musawi, Hussein Ali Nour (ALBAHITH ALALAMI, 2022)
This article explores the role of talk shows in setting the public’s agenda regarding political mobilization in Iraq. The researcher designed a questionnaire that contains both closed and open-ended questions to allow respondents to express their opinions more freely. The researcher chose a phased purposive sample consisting of 294 respondents. The data was then subjected to analysis and verification using the Statistical Package for the Social Sciences (SPSS).